1993
DOI: 10.1177/000992289303200802
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Extrapulmonary Presentations Of Severe Respiratory Syncytial Virus Infection Requiring Intensive Care

Abstract: The patterns and nature of a four-month epidemic of severe respiratory syncytial virus (RSV)-associated disease were analyzed using presenting, demographic, clinical, and therapeutic data. Of 218 infants with RSV infection admitted to Rainbow Babies and Childrens Hospital, 49 (22.4%), most born prematurely, entered the pediatric intensive care unit (PICU). Fluorescent antibody and/or enzyme-linked immunosorbent assay documented RSV infection. PICU patients underwent airway stabilization; 53.5% were intubated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 22 publications
0
22
0
1
Order By: Relevance
“…Of these, 5 infants were recruited from the MICU, 6 were recruited from the ICP, and 4 from the Inpatient Units. There were 10 males and 5 females with a median age of 2.0 (0.4-18) months, median weight of 5.8 (3)(4)(5)(6)(7)(8)(9)(10)(11) kg and median height of 60 (50-84) cm. Median time to acute stabilization was 4 (1-6) days, time between initial and final CO recording was 2.5 (0.8-7.2) days and length of hospitalization was 3.6 (1.6-8.9) days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 5 infants were recruited from the MICU, 6 were recruited from the ICP, and 4 from the Inpatient Units. There were 10 males and 5 females with a median age of 2.0 (0.4-18) months, median weight of 5.8 (3)(4)(5)(6)(7)(8)(9)(10)(11) kg and median height of 60 (50-84) cm. Median time to acute stabilization was 4 (1-6) days, time between initial and final CO recording was 2.5 (0.8-7.2) days and length of hospitalization was 3.6 (1.6-8.9) days.…”
Section: Resultsmentioning
confidence: 99%
“…In most cases these infants are admitted to the hospital for respiratory distress and hypoxia; however, RSV has been reported to produce myocarditis [2] or is associated with myocardial injury [3], arrhythmias [4,5], and viral-induced sepsis [6]. Infants with respiratory insufficiency from bronchiolitis may have similar clinical features to infants with congestive heart failure [7], presenting with irritability, fever, tachypnea, tachycardia and a mottled appearance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, RSV infection and the age parameters may influence the clinical course in those patients who have no nosocomial infection. Another study reported hypothermia as the predominant symptom present in 49 babies admitted into an NICU, half of whom had been born prematurely, but the authors did not check for bradycardia [20].…”
Section: Discussionmentioning
confidence: 98%
“…6 They are present with low grade fever, hypothermia in younger infants, running nose, and irritating cough. 7,8 Concomitant otitis media is common. 8 Apnea may occur particularly in low-birth weight and preterm babies.…”
mentioning
confidence: 99%